U’Ductor: um modelo para cuidado ubíquo de doenças crônicas não transmissíveis - Vianna, Henrique Damasceno (Universidade do Vale do Rio dos Sinos, 2013)
Accordingly with the World Health Organization, heart disease, chronic respiratory diseases, cancer and diabetes are the most common non-communicable diseases and one of the leading causes of the mortality in the world. In such cases we need more than patient engagement to help to control of the disease, community and health organizations support is also desirable. These roles must support the patients self-management activities, making them feel confident and motivated. This support can be accomplished by ubiquitous computing. The ubiquitous computing gives conditions to help chronic diseases patients in the management of their activities, offering support to them anytime, anywhere. This work presents U’Ductor, a model for supporting ubiquitous non-communicable disease care, whose goal is to help the integration between patient and community resources. The U’Ductor gives a step forward in relation to the studied related works by integrating patients, community resources and community members. Those features were not completely explored in the studied works in the way it’s employed in U’Ductor. An implementation of the model was evaluated by chronic patients, which had given a positive feedback about it.
Keywords: Computação ubíqua; Gerenciamento de doenças crônicas; Ubiquitous computing; Chronic disease management; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação